2022
DOI: 10.1111/1365-2745.13932
|View full text |Cite
|
Sign up to set email alerts
|

Graminoids vary in functional traits, carbon dioxide and methane fluxes in a restored peatland: Implications for modelling carbon storage

Abstract: 1. One metric of peatland restoration success is the re-establishment of a carbon sink, yet considerable uncertainty remains around the time-scale of carbon sink trajectories. Conditions post-restoration may promote the establishment of vascular plants such as graminoids, often at greater density than would be found in undisturbed peatlands, with consequences for carbon storage. Although graminoid species are often considered as a single plant functional type (PFT) in landatmosphere models, our understanding o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…Specifically, two strategies with similar growth and leaf area differed in height, suggesting that leaf area may be most predictive for plants that invest primarily in photosynthesizing leaf biomass, while plant height may be most effective for plants investing in more structural stem biomass. These results are consistent with previously observed positive associations between ecosystem productivity and leaf area (Goud et al, 2017;Litton et al, 2008) and height (Goud, Touchette, et al, 2022;Westoby, 1998).…”
Section: Strategysupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, two strategies with similar growth and leaf area differed in height, suggesting that leaf area may be most predictive for plants that invest primarily in photosynthesizing leaf biomass, while plant height may be most effective for plants investing in more structural stem biomass. These results are consistent with previously observed positive associations between ecosystem productivity and leaf area (Goud et al, 2017;Litton et al, 2008) and height (Goud, Touchette, et al, 2022;Westoby, 1998).…”
Section: Strategysupporting
confidence: 93%
“…Both leaf N and P are predicted to positively correlate with growth due to the functional need for N and P in photosynthesis (Walker et al, 2014; Wright et al, 2004). However, nonlinear or insignificant relationships are frequently reported (Feng & Dietze, 2013; Goud, Touchette, et al, 2022; Midgley et al, 2004). Here, growth was negatively associated with leaf N and P (Figure 1G–I; Table 2), which has been observed for other herbaceous species grown under common conditions (Poorter et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…and other mosses (Berger et al, 2018; Laine et al, 2016). Previous long‐term studies using a PFT approach have demonstrated that peatland vascular PFTs (graminoids and shrubs) control gaseous methane emissions (Armstrong et al, 2015; Goud et al, 2021; Robroek et al, 2015), while increased Sphagnum moss coverage reduces fluvial dissolved organic carbon (DOC) effluxes (Dunn et al, 2016). Furthermore, peatland carbon cycling may be constrained by ericoid shrubs presence, as increased gross CO 2 fluxes from graminoids were observed during selective removal experiments of key PFTs, that is, ericoid shrubs (Ward et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…‐ Couple measurements of above‐ and belowground traits : Investigating the relationship between above‐ and belowground traits may help in determining the best aboveground proxies for belowground wetland CH 4 dynamics. Relevant aboveground traits to be connected to root traits could include vascular plant green area (Goud et al., 2017; Malhotra & Roulet, 2015), plant height (Chen et al., 2009; Goud et al., 2022), stem diameter and number per plot (Noyce et al., 2023; Pangala et al., 2013, 2015), and photosynthetic rate (Sutton‐Grier & Megonigal, 2011), as well as aboveground biomass (e.g., Joabsson & Christensen, 2001; Sutton‐Grier & Megonigal, 2011). Trees add to the complexity of ecosystem CH 4 emissions, as their stems can emit CH 4 , even when the soil consumes CH 4 (Covey & Megonigal, 2018).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%